2009
DOI: 10.1177/0095244308091524
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Complex Curatives on the Properties for Ethylene Propylene Diene Rubber/Polypropylene Blends

Abstract: This study investigates the effects of different types of curatives at polypropylene (PP) and ethylene propylene diene monomer (EPDM) blend ratios (100 : 40 phr) in dynamically vulcanized products. The thermoplastic vulcanizates are prepared by batch melt mixing of PP with EPDM, using pheolic resin, dicumyl peroxide, hydrosilyation, and complex systems as curatives. Observed changes in curing characteristics and mechanical properties of blends have been correlated with phase morphology, as attested by scanning… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Our earlier work found the vulcanizing characteristics, mechanical properties, morphologies, intermolecular interactions, and thermal properties of EPDM/PP blends to be related to the added curatives (peroxides, phenolic resins, and hydrosilylation) [31]. Experimental results showed that the properties of EPDM/PP blends could be controlled using complex curatives to make improvements.…”
Section: Introductionmentioning
confidence: 94%
“…Our earlier work found the vulcanizing characteristics, mechanical properties, morphologies, intermolecular interactions, and thermal properties of EPDM/PP blends to be related to the added curatives (peroxides, phenolic resins, and hydrosilylation) [31]. Experimental results showed that the properties of EPDM/PP blends could be controlled using complex curatives to make improvements.…”
Section: Introductionmentioning
confidence: 94%